Treadmill exercise promotes neuroprotection against cerebral ischemia–reperfusion injury via downregulation of pro-inflammatory mediators - Zhang Y; Cao RY; Jia X; Li Q; Qiao L; Yan G; Yang J (Neuropsychiatric Disease and Treatment)
Ying Zhang,1,* Richard Y Cao,2,* Xinling Jia,3,* Qing Li,1 Lei Qiao,1 Guofeng Yan,4 Jian Yang1 1Department of Rehabilitation, 2Laboratory of Immunology, Shanghai Xuhui Central Hospital, Shanghai Clinical Research Center, Chinese Academy of Sciences, 3School of Life sciences, Shanghai University, 4School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China *These authors contributed equally to this work Background: Stroke is one of the major causes of morbidity and mortality worldwide, which is associated with serious physical deficits that affect daily living and quality of life and produces immense public health and economic burdens. Both clinical and experimental data suggest that early physical training after ischemic brain injury may reduce the extent of motor dysfunction. However, the exact mechanisms have not been fully elucidated. The aim of this study was to investigate the effects of aerobic exercise on neuroprotection and understand the underlying mechanisms.Materials and methods: Middle cerebral artery occlusion (MCAO) was conducted to establish a rat model of cerebral ischemia–reperfusion injury to mimic ischemic stroke. Experimental animals were divided into the following three groups: sham (n=34), MCAO (n=39), and MCAO plus treadmill exercise (n=28). The effects of aerobic exercise intervention on ischemic brain injury were evaluated using functional scoring, histological analysis, and Bio-Plex Protein Assays.Results: Early aerobic exercise intervention was found to improve motor function, prevent death of neuronal cells, and suppress the activation of microglial cells and astrocytes. Furthermore, it was observed that aerobic exercise downregulated the expression of the cytokine interleukin-1β and the chemokine monocyte chemotactic protein-1 after transient MCAO in experimental rats.Conclusion: This study demonstrates that treadmill exercise rehabilitation promotes neuroprotection against cerebral ischemia–reperfusion injury via the downregulation of pro-inflammatory mediators. Keywords: rehabilitation, cytokine, chemokine, stroke, rat model